Customized Barrier Membrane (Titanium Alloy, Poly Ether-Ether Ketone and Unsintered Hydroxyapatite/Poly-l-Lactide) for Guided Bone Regeneration - Shi, Yilin; Liu, Jin; Du, Mi; Zhang, Shengben; Liu, Yue; Yang, Hu; Shi, Ruiwen; Guo, Yuanyuan; Song, Feng; Zhao, Yajun; Lan, Jing (Frontiers in Bioengineering and Biotechnology, 2022)
Sufficient bone volume is indispensable to achieve functional and aesthetic results in the fields of oral oncology, trauma, and implantology. Currently, guided bone regeneration (GBR) is widely used in reconstructing the alveolar ridge and repairing bone defects owing to its low technical sensitivity and considerable osteogenic effect. However, traditional barrier membranes such as collagen membranes or commercial titanium mesh cannot meet clinical requirements, such as lack of space-preserving ability, or may lead to more complications. With the development of digitalization and three-dimensional printing technology, the above problems can be addressed by employing customized barrier membranes to achieve space maintenance, precise predictability of bone graft, and optimization of patient-specific strategies. The article reviews the processes and advantages of three-dimensional computer-assisted surgery with GBR in maxillofacial reconstruction and alveolar bone augmentation; the properties of materials used in fabricating customized bone regeneration sheets; the promising bone regeneration potency of customized barrier membranes in clinical applications; and up-to-date achievements. This review aims to present a reference on the clinical aspects and future applications of customized barrier membranes.